Комбінація фотограметрії та камери Kinect для покращеного 3D-сканування - Бобнєв, Р. О.; Старкова, А. В. (ХНУРЕ, 2025)
This paper explores the integration of photogrammetry and Kinect technology for enhanced 3D scanning. Photogrammetry relies on image analysis, while Kinect provides real-time depth data. Combining these methods improves accuracy, reduces computational costs, and enhances reconstruction in low-texture environments. Experimental results show a 15-20% error reduction compared to traditional photogrammetry. This approach offers new possibilities for efficient and high-quality 3D modeling.
Keywords: фотограметрія; 3D-сканування